No exit from the joint decision trap? Can German federalism reform itself? - Fritz W. Scharpf (Max Planck Institute for the Study of Societies, 2005)
The unique institutions that make up Germany's unitary federal state, long considered part of the country's post-war success story, are now generally perceived as a joint-decision trap impeding effective policy responses to new economic and demographic challenges at both levels of government. Nevertheless, a high-powered bicameral Commission set up in the fall of 2003 failed to reach agreement on constitutional reforms. The paper analyzes the misguided procedural and substantive choices that led to this failure, and it discusses the possibility of asymmetric constitutional solutions that might enhance the capacity for autonomous action at both levels. – – Die im internationalen Vergleich einmaligen Institutionen des unitarischen Bundesstaats erschienen lange as Element der deutschen Erfolgsgeschichte in der Nachkriegszeit. Heute erscheinen sie jedoch als Politikverflechtungsfalle, welche die Politik in Bund und Ländern an der Bewältigung der neuen ökonomischen und demographischen Herausforderungen hindert. Trotzdem gelang es einer im Herbst 2003 eingesetzten und politisch potent besetzten gemeinsamen Kommission von Bundestag und Bundesrat nicht, sich auf eine Verfassungsreform zu einigen. Der Text analysiert die prozeduralen und sachlichen Fehlentscheidungen, die das Scheitern erklären, und er erörtert die Möglichkeit asymmetrischer Lösungen, die den Spielraum für autonomes politisches Handeln auf beiden staatlichen Ebenen erweitern könnten.
Keywords: 300